COMPARATIVE ANALYSIS OF OVERBURDEN VOLUME BASED ON SURVEY AND TRUCK COUNT METHODS - Andre Yerickho Simorangkir jimmy simorangkir; Gina Audina P Alhabsyi; Muh. Arif Idhan (Fakultas Teknik UPRI, 2026)
This study aims to analyze the comparison of overburden volume based on survey and truck count methods. The background of this research is the importance of accurate overburden volume calculation to support production planning and control in open pit mining, due to potential deviations arising from different calculation methods. This research uses a descriptive quantitative method. Data were obtained from topographic surveys using a total station processed with Surpac 6.3.2 software and production data based on truck haulage records, hauling capacity, and material density. The analysis was carried out by comparing the results of both methods. The results show that the overburden volume calculated by the survey method was 26,079 BCM, while the truck count method resulted in 30,718 BCM, with a deviation of -17.788%. This difference is influenced by survey accuracy, truck load variation, and haulage recording accuracy.